Autocratic Leadership and Employee Performance: Moderating Role of Age Group - Shrestha, Anisha; Pandey, Nabin; Gurung, Bimla Kumari; Kharel, Sagar (International Research Journal of MMC, 2024)
Employee performance is crucial for organizational effectiveness, quality and efficiency at the task level. This study aims to provide an inclusive understanding on how autocratic leadership (AL) impacts on employee performance (EP) and whether age moderates this impact. It develops a simple regression model and accesses the dummy indicator regression of the variable used and discusses the result of the analysis of Autocratic Leadership and Employee Performance. This study uses primary data collected through likert scale and analyses using IBM SPSS statistics version 25. Similarly, the secondary data were collected through books, journal articles and websites. This study finds that AL has a positive and significant impact on EP with the value of coefficient of multiple determinations 0.111. Furthermore, this study successfully confirms that the moderating variable, age group, had no role on effects of AL on EP shown by the dummy indicator regression analysis. Finally, this study emphasizes the need for further rigorous research to understand the impact of autocratic leadership on employee performance, offering insights beneficial to both academics and organizational managers.